Fireside issues in advanced power generation systems. (1st July 2013) - Simms, N J; Sumner, J; Hussain, T; Oakey, J E
<x xml:space="preserve">Abstract</x> The requirements to supply increasing quantities of electricity and simultaneously to reduce the environmental impact of its production are currently major issues for the power generation industry. Routes to meeting these challenges include the development and use of power plants with ever increasing efficiencies coupled with the use of both a wider range of fuels and technologies designed to minimise CO2 emissions. For fireside hot gas path components, issues of concern include deposition, erosion and corrosion in novel operating environments and increased operating temperatures. The novel operating environments will be produced both by the use of new fuel mixes and by the development of more complex gas pathways (e.g. in various oxyfired or gasification systems). Higher rates of deposition could significantly reduce heat transfer and increase the need for component cleaning. However, degradation of component surfaces has the potential to be life limiting, and so such effects need to be minimised. Materials and operational issues related to these objectives are reviewed.